The Students’ Experiences in Implementing Duolingo-Assisted Listening Learning - Sukarya, Deni; Kamil, Acep Bahrum; Utami, Praditya Putri (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
Technology has evolved and produced a wide range of devices to enhance education and teaching methods that can assist students in learning languages. This study aims to describe students’ experiences in implementing Duolingo-assisted Listening learning. The participants of this research were three Junior high school students in Karawang. The method and design in this research are to use descriptive qualitative research conducted through Observation, interviews, and Questionnaires. This research analyzes the data using thematic analysis. The findings showed that the participants initially had difficulty listening, and after Duolingo-assisted, students were happy, easier, excited, and motivated to learn listening skills using Duolingo. Due to the gamification of learning and listening exercises provided by Duolingo, students find it easier to learn listening. Because it offers students new experiences in learning English, Duolingo is an effective tool for use in the classroom. In conclusion, this study indicates that students have positive experiences implementing Duolingo-assisted Listening Learning.